Sosialisasi Transaksi Ekonomi Yang Sesuai Dengan Prinsip Ekonomi Syariah Pada Siswa SMKN 1 Tapung - Khairi, Rifqil; Winario, Mohd; Zakir, Muhammad; Sudirman, Wahyu Febri Ramadhan; Fitriyana, Rinda; Amalia, Nala; Irmawanti, Irmawanti (Journal of Community Sustainability, 2025)
This community service activity was carried out for the students of SMKN 1 Tapung Kampar, Riau Province. The purpose of this program is to provide knowledge and enhance understanding of the concept of Islamic Economics among the community, especially Generation Z, represented by the students of SMKN 1 Tapung Kampar. The methods used in this community service activity included counseling and presentations, discussions, as well as practice sessions (pre-test and post-test) for the participants. The results of this program show that the community service activities were successfully implemented and ran smoothly according to the planned schedule. The findings indicate that: First, most students of SMKN 1 Tapung Kampar do not yet have a good understanding of the concept of Islamic economics. Second, the objectives of the community service program were achieved, as all activities were conducted through collaboration between the school and the facilitators, and were carried out according to the event rundown and the predetermined schedule.